2021
DOI: 10.1002/ecy.3319
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity facilitates carnivore coexistence

Abstract: Competitively dominant carnivore species can limit the population sizes and alter the behavior of inferior competitors. Established mechanisms that enable carnivore coexistence include spatial and temporal avoidance of dominant predator species by subordinates, and dietary niche separation. However, spatial heterogeneity across landscapes could provide inferior competitors with refuges in the form of areas with lower competitor density and/or locations that provide concealment from competitors. Here, we combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 65 publications
4
35
1
Order By: Relevance
“…For example, the range at which a source of risk or reward is directly perceivable should dictate the scale at which direct responses occur—for difficult to perceive sources of risk and reward, memory and learning may allow an animal to use indirect assessments to respond at greater scales than would be possible with direct assessments. Despite combining two potentially different scales of assessment (i.e., direct vs. indirect), our first analysis was consistent with contemporary methods of evaluating risk‐avoiding and reward‐seeking tactics (Davies et al, 2021 ). Importantly, we compared the results of this analysis with direct inferences drawn from analyses in the following two assessments.…”
Section: Methodssupporting
confidence: 75%
See 2 more Smart Citations
“…For example, the range at which a source of risk or reward is directly perceivable should dictate the scale at which direct responses occur—for difficult to perceive sources of risk and reward, memory and learning may allow an animal to use indirect assessments to respond at greater scales than would be possible with direct assessments. Despite combining two potentially different scales of assessment (i.e., direct vs. indirect), our first analysis was consistent with contemporary methods of evaluating risk‐avoiding and reward‐seeking tactics (Davies et al, 2021 ). Importantly, we compared the results of this analysis with direct inferences drawn from analyses in the following two assessments.…”
Section: Methodssupporting
confidence: 75%
“…Despite likely occurring at a greater scale, we were still not able to capture the direct perception of coyotes toward kills made by mountain lions. In a recent study where direct and indirect responses were framed as “reactive” and “proactive,” respectively, African wild dogs ( Lycaon pictus ) avoided the risk of predation from African lions ( Panthera leo ) using indirect rather than direct responses to risk when both were compared within iSSF analyses (Davies et al, 2021 ). As is indicated by the framing of direct responses as “reactive”, direct responses are perhaps more likely to occur at finer spatiotemporal scales than indirect responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial heterogeneity in the landscape may also play a key role in facilitating carnivore coexistence through the availability of different habitats and other physical features, as well as uneven resource distribution (Chesson, 2000; Stein et al., 2014) which can provide vital refuges for subordinate species to reduce encounters with dominant carnivores (Davies et al., 2021; Durant, 1998). Our results indicated that spatial avoidance was slightly higher in the fynbos biome compared to the karoo which is likely due to the landscape heterogeneity which provides more refugia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystems are complex and spatially heterogeneous, and spatial heterogeneity can have decided consequences for ecosystem functioning (Hunter and Price 1992, Turner and Chapin 2005, Chapin et al 2011). The degree of heterogeneity at the landscape scale can influence community dynamics (Hastings 1977, Turner and Gardner 2015), species coexistence (Davies et al 2021) and resilience to environmental change (van Nes and Scheffer 2005). Much effort, especially, has been devoted to characterizing how landscape‐scale spatial heterogeneity impacts wildlife population persistence and community dynamics (Hutchings et al 2000), with the goal of understanding how habitat should be protected to best support species of conservation concern (Lovett et al 2005).…”
Section: Introductionmentioning
confidence: 99%